Phanerozoic evolution model of a stressstrain state of the Earth crust at the Dnieper-Donets paleorift - Bartashchuk, O.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
Structural manifestation of the planetary fracture net in the Dnieper-Donets paleorift (DDP) is studied on the basis of a statistical analysis of the azimuthal distribution of the Precambrian basement faults and the sedimentary cover on rosediagrams and maps. The stressstrain state of the continental crust at Phanerozoic is reconstructed, the spacetime inversion of the parameters of the field of tectonic stresses is determined, due to the rotational mechanism of planetary deformations. The geotectonic peculiarity of the evolution of DDP is the formation of three structural plans: the rift (D3—C1), inversionplatform (C2—P), and collisional (MZ—KZ) ones with the determining role of the horizontalaxial tectonics. A conceptual model of the geodynamic evolution of DDP has been created as a theoretical basis for the geodynamic modeling and the geotectonic and oilgasgeological zonings.